LEVERAGING THE POTENTIALS OF ARTIFICIAL INTELLIGENCE-POWERED TECHNOLOGIES FOR SCIENCE TEACHING AND LEARNING IN SOUTH EAST NIGERIA (IJOVTECH, 2026)
The adoption of artificial intelligence (AI)-driven technologies in science instruction has been revealed to be a radical solution to the longstanding issues of teaching and learning with regard to resource-based issues in some areas such as South East Nigeria. This paper investigates how artificial intelligence, through adaptive learning systems, intelligent learning, and virtual simulation, could improve the learning process of science courses and student achievement. Based on a mixed-method design, the primary data were observed in the form of questionnaires and the survey of 200 teachers of science and 500 students of secondary schools in the five states of South East Nigeria (Abia, Anambra, Ebonyi, Enugu and Imo). The model of action thus assumed is the Technological Pedagogical Content Knowledge (TPACK) model that focuses on synergy of technology, pedagogy and content knowledge as a means of successful integration. Results show that the application of AI technologies can be used to create personalized learning, automate assessment, and promote critical thinking, yet the implementation is hindered by the lack of infrastructure, insufficient teacher training, and digital divide. Demographics of the participants shows that it has a good concentration of male teachers (62%), with average of 12 years experience whereas the students are well balanced in terms of gender; however they can access technology differently depending on the urban to rural geographical differences. The paper mentions such positive outcomes as better interaction and acquisition of skills and is consistent with global trends in AI and education and deals with specific realities of economic transformation in Nigeria. The policy interventions that are recommended are the AI infrastructure and professional development. The study is relevant to the debate when it comes to the fair and balanced integration of AI in developing settings, which facilitates sustainable educational progress.